"Fear-of-the-State Bias" in Survey Data. (16th December 2017) - Zimbalist, Zack
Abstract: Public attitude surveys provide invaluable data for assessing how people view their countries' democratic progress and government performance, in addition to a range of other outcomes. Yet, these data are vulnerable to substantial biases deriving from interviewer effects. Apart from social desirability bias resulting from a (non)coethnic interviewer, this article demonstrates that the perception of a government interviewer is another crucial mechanism that generates bias in the African context. The evidence suggests that fear of the state, rather than social desirability, leads people in less open societies to provide more positive assessments of democratic and government performance and underreport corruption. In identifying this new source of bias, the article discusses potential improvements to survey protocols and modes of administration.